10 kV AC test verification of the high temperature superconducting fault current limiter with bias magnetic field. (December 2020) - Dong, Yujun; Zhu, Jiahui; Wei, Defu; Chen, Wei; Du, Qingqing; Zhang, Ke; Chen, Panpan; Lu, Kun; Jiang, Hao; Wang, Shuai; Liu, Jiaxing; Guo, Tie; et al.
Highlights: 10 kV operation test of SFCL with bias magnetic field was achieved. Results shown the limiting resistance is 1.21 Ω within 10 ms fault time. Quench response time is less than 5 ms. Abstract: Under the support of the China State Grid Corporation Science and Technology Project, a set of 10 kV superconducting fault current limiter (SFCL) with bias magnetic field including a high temperature superconducting a low inductance unit, a double split reactor, a fast breaker and its control system is designed and assembled in Hushitai high voltage center of Electric Power Research Institute of State Grid Liaoning Electric Power Co., Ltd. The 10 kV dedicated test including high voltage test, phase to phase short circuiting fault test, quench resistance measurement, quench recovery time measurement were performed in December 2019. The fault current distribution and voltage test results during the phase to phase short-circuit fault of the SFCL are presented and analyzed. Test results indicate that current limiting resistance of SFCL unit is about 1.21 Ω within 10 ms fault time. Those results meet the design requirement.